A rare case of stage IV erythrodermic folliculotropic cutaneous T-cell lymphoma presenting in childhood: Importance of a multidisciplinary approach. - Scarisbrick, J.J.; Amel-kashipaz, R.; Rudzki, Z.; Mur, R.; Burkill, G.; Lane, P.; Richter, A.; Chaganti, S. (European Journal of Pediatric Dermatology, 2024)
Cutaneous T-cell lymphoma (CTCL) typically presents in the sixth to seventh decades, but may begin in childhood. Even rarer in children is the erythrodermic form of CTCL, which must be suspected in the presence of folliculotropism and peripheral lymphadenopathy. We describe a fatal case of folliculotropic erythrodermic CTCL in a 17-year-old boy.